Psalms 42-72: an international theological commentary - Elliott, Mark W. (T&T Clark International Theological Commentary Series, 2024)
Cover -- Half title -- Title -- Copyright -- Contents -- General Editors' Preface -- Acknowledgements -- Select Bibliography -- Introduction to Theological Commentary on Psalms 42-72 -- Psalm 42 -- Psalm 43 -- Psalm 44 -- Psalm 45 -- Psalm 46 -- Psalm 47 -- Psalm 48 -- Psalm 49 -- Psalm 50 -- Psalm 51 -- Psalm 52 -- Psalm 53 -- Psalm 54 -- Psalm 55 -- Psalm 56 -- Psalm 57 -- Psalm 58 -- Psalm 59 -- Psalm 60 -- Psalm 61 -- Psalm 62 -- Psalm 63 -- Psalm 64 -- Psalm 65 -- Psalm 66 -- Psalm 67 -- Psalm 68 -- Psalm 69 -- Psalm 70 -- Psalm 71 -- Psalm 72.